Digitized but disconnected: CSR platform governance and environmental exclusion in oil-producing villages of Indonesia - Harirah, Zulfa; Gusmansyah, Gusmansyah (Journal of Environment and Sustainability Education, 2026)
This study examines why digitally mediated corporate social responsibility (CSR) governance has failed to address structural and ecological problems in oil- and gas-producing villages in Riau Province, Indonesia. Oil and gas corporations formally articulate commitments to social and environmental responsibility in official policy documents; however, their corporate social responsibility (CSR) initiatives are predominantly symbolic in nature and tend to be constrained to short-term, project-based interventions such as vocational training, food assistance, and basic road infrastructure development. These interventions do not engage with the structural drivers of environmental degradation, persistent poverty, and the absence of a locally grounded green transition. Methodologically, the research employs a qualitative design, drawing on semi-structured interviews with village authorities, residents, and officials from the Riau Provincial Government. The analysis further incorporates a documentary review of policy texts, CSR implementation reports, and digital CSR governance platforms. The data were analyzed to identify exclusionary mechanisms and disjuncture between formal governance architectures and actual CSR practices. The findings demonstrate that although digital CSR systems formally enhance transparency and open channels for participation, villagers’ engagement is largely confined to the submission of administrative proposals, with no meaningful avenues for deliberation, co-decision-making, or inclusive oversight. Decision-making authority remains concentrated in the hands of corporate actors and local elites, frequently mediated through political recommendations issued by local government leaders. In response to these dynamics, the study advocates a reconfiguration toward “participatory digital governance,” in which digital CSR platforms are mandated to incorporate community-led monitoring, binding feedback loops, and direct accountability mechanisms.